The Other Side of Jazz Canon – Narrative Without Women - Jovićević, Jasna (Res Facta Nova, 2025)
Despite concerted efforts aimed at diversifying the jazz genre, women persistently occupy a marginalized position, often relegated to the periphery within a predominantly male-centric narrative. The historical trajectory of jazz has been profoundly shaped by patriarchal ideologies, perpetuating a discourse that predominantly exalts male musicians as virtuosic pioneers. Educational institutions persist in repeating a historical lens established in the 1960s, further solidifying the canonization of male brilliance. This narrative framework tends to spotlight individual soloists while disregarding the significant contributions of women, especially instrumentalists, engendering a sense of historical disjunction within the jazz tradition. This article advocates for a comprehensive reevaluation of jazz historiography, one that intricately examines and integrates the substantial contributions of female players. By doing so, it aims to challenge the entrenched male dominated canonized version and cultivate a more inclusive comprehension of jazz music's diverse heritage.